1991
DOI: 10.1002/tl.37219914703
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of the seven principles for good practice in undergraduate education

Abstract: The development of the Seven Principles for Good Practice in Undergraduate Education has been a collaborative effort among researchers, faculty members, and administrators from a wide range of U.S. colleges and universities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 3 publications
0
29
0
1
Order By: Relevance
“…The students learned that they could have fun while using the technical and analytical skills acquired in class to isolate and identify organisms from an environmental source of their own choice. The group presentation and peer evaluations demonstrated the effectiveness of their interpersonal communication (13) and cooperative learning (11), while the paper assessed each student's critical thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…The students learned that they could have fun while using the technical and analytical skills acquired in class to isolate and identify organisms from an environmental source of their own choice. The group presentation and peer evaluations demonstrated the effectiveness of their interpersonal communication (13) and cooperative learning (11), while the paper assessed each student's critical thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, researchers have found that such social interaction advances individual cognitive development, which spawns greater academic achievement than do most conventional learning activities (Dansereau, 1983;Johnson & Johnson, 1983;Slavin, 1983;Frierson, 1986;Triesman, 1986). In 1986, Chickering and Gamson, in the company of a panel of nationally recognized scholars, pulled a solid base of longstanding research together to arrive at the Seven Principles of Good Practice in Undergraduate Education (Gamson, 1991). Good practice, they surmised, encourages student-faculty contact, co-operation among students, active learning and prompt feedback.…”
Section: The Unconventional Wisdom Of Collaborately Active Learningmentioning
confidence: 97%
“…According to (Tanabe, 1997) (Gramigna, 1993) (Gamson, 1991), business simulation games characteristics [24] [12] [11]:…”
Section: Literature Reviewmentioning
confidence: 99%